1998
DOI: 10.1152/jappl.1998.84.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea in obese miniature pigs

Abstract: We postulated that three extremely obese Yucatan miniature pigs would have more sleep apnea than three nonobese Yucatan miniature pigs. Pigs were studied with the use of electroencephalograms, inductance plethysmography, oximetry, expired nasal CO2, or thermistors. All of the obese pigs, but none of the nonobese pigs, had both sleep apnea (8.5, 10.3, and 97.0 in obese pigs vs. O apnea + hypopnea/h in all nonobese pigs; P < 0.05) and oxyhemoglobin desaturation episodes during sleep [9.4 +/- 3.0 vs. 0 + 0.53 (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 24 publications
1
37
1
1
Order By: Relevance
“…Other animals develop OSA with the development of obesity, in an analogous manner to humans. For example, Lonergan and colleagues (11) reported that female Yucatan miniature pigs developed OSA (Figure 1). Two obese pigs exhibited OSA with an overall AHI of approximately 9 and a REM AHI of approximately 27, whereas a third pig exhibited severe central sleep apnea.…”
Section: Animals With Spontaneous Sleep Apneamentioning
confidence: 99%
“…Other animals develop OSA with the development of obesity, in an analogous manner to humans. For example, Lonergan and colleagues (11) reported that female Yucatan miniature pigs developed OSA (Figure 1). Two obese pigs exhibited OSA with an overall AHI of approximately 9 and a REM AHI of approximately 27, whereas a third pig exhibited severe central sleep apnea.…”
Section: Animals With Spontaneous Sleep Apneamentioning
confidence: 99%
“…This effect of obesity is found not only in humans but has also been observed in several animal models of obesity. Airway narrowing and increased collapsibility have been shown in the obese Zucker rats (9)(10)(11)(12), and increased upper airway resistance has been demonstrated in obese pigs (13,14).…”
mentioning
confidence: 99%
“…In isolated canine, feline, rat, and rabbit upper airway preparations, the mechanical effects of lingual displacement, tracheal traction, and extraluminal tissue pressure (18 -20, 42, 42, 54, 56) and the neuromuscular effects of alterations in gas exchange and airway pressure (1, 6, 8 -10, 43, 51) on pharyngeal collapsibility have been demonstrated. Studies in pigs and bulldogs highlight the impact of structural narrowing on upper airway patency, particularly when neuromuscular activity wanes during rapid eye movement (REM) sleep (14,24,58). Recently, investigators have demonstrated that obesity can also impose structural loads on the airway (5) that elevate pharyngeal collapsibility in the fa/fa rat and that serotonergic mechanisms can offset this mechanical effect (27).…”
mentioning
confidence: 99%